2018
DOI: 10.1002/micr.30387
|View full text |Cite
|
Sign up to set email alerts
|

A basic fibroblast growth factor slow‐release system combined to a biodegradable nerve conduit improves endothelial cell and Schwann cell proliferation: A preliminary study in a rat model

Abstract: Background A basic fibroblast growth factor (bFGF) slow‐release system was combined to a biodegradable nerve conduit with the hypothesis this slow‐release system would increase the capacity to promote nerve vascularization and Schwann cell proliferation in a rat model. Materials and Methods Slow‐release of bFGF was determined using Enzyme‐Linked ImmunoSorbent Assay (ELISA). A total of 60 rats were used to create a 10 mm gap in the sciatic nerve. A polyglycolic acid‐based nerve conduit was used to bridge the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Besides biodegradable nerve conduit, a search for use of decellularized allogenic nerve matrix seeded with bone marrow derived mesenchymal stem cells has been explored by bridging a 20 mm sciatic nerve gap in rats (Kaizawa et al, ). Moreover, biodegradable nerve conduits have been greatly developed with growth factors in the past decades, which includes our recent experiment on the biodegradable nerve conduit with a basic fibroblast growth factor slow‐release system (Fukuda, Kusuhara, Nakagoshi, Isogai, & Sueyoshi, ). Basic fibroblast growth factor (bFGF) is a cytokine that accelerates angiogenesis (Gospodarowicz, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides biodegradable nerve conduit, a search for use of decellularized allogenic nerve matrix seeded with bone marrow derived mesenchymal stem cells has been explored by bridging a 20 mm sciatic nerve gap in rats (Kaizawa et al, ). Moreover, biodegradable nerve conduits have been greatly developed with growth factors in the past decades, which includes our recent experiment on the biodegradable nerve conduit with a basic fibroblast growth factor slow‐release system (Fukuda, Kusuhara, Nakagoshi, Isogai, & Sueyoshi, ). Basic fibroblast growth factor (bFGF) is a cytokine that accelerates angiogenesis (Gospodarowicz, ).…”
Section: Discussionmentioning
confidence: 99%
“…bFGF‐gelatin microsphere complex is released slowly according to the degradation speed of gelatin and the pharmacological activity of bFGF can therefore be maintained for 2 weeks (Tabata et al, ). The in vivo study using the nerve conduit with bFGF slow‐release system demonstrated that the migration distance for both vascular endothelial cells and Schwann cells, and the elongation distance of axons were accelerated in the early phase of nerve regeneration (within 4 weeks after implantation) (Fukuda et al, ). With a growing interest in the clinical potential of mesenchymal stem cells derived from bone marrow (Kaizawa et al, ), adipose tissue (Kappos et al, ; Saller et al, ), and menstrual blood (Farzamfar et al, ), the utilization of these stem cells into biodegradable nerve conduits with FGF slow‐release system may offer a promising technique to enhance nerve regeneration with biodegradable nerve conduits.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that an adequate blood supply is important to nerve regeneration (Tassi et al, 2001). bFGF is a cytokine that accelerates angiogenesis (Gospodarowicz, 1991) and contributes to the proliferation of undifferentiated SCs (Fukuda, Kusuhara, Nakagoshi, Isogai, & Sueyoshi, 2018;Li et al, 2017). So more vascular regeneration stimulated, more SCs will migrate to nerve injury area through the blood vessels and dedifferentiate to a stem-like cell, which is benefit for nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that one of the limiting factors is the ability to supply enough nutrients and oxygen to facilitate axon growth. Research has shown that vascular networks within NGCs can be enhanced in the early post-transplantation period by including vascular bundles in the graphs [127]. Consequently, increased vascularity of nerve grafts has been demonstrated to improve overall nerve regeneration and axonal elongation [128,129].…”
Section: Surgical Intervention a Vascularizationmentioning
confidence: 99%